Elevated soluble ACE2 activity in children and adults after SARS-CoV-2 exposure irrespective of laboratory-confirmed infection: research article - Stich, Maximilian; Magalhães, Vladimir Gonçalves; Bürger, Friederike; Garbade, Sven; Jeltsch, Kathrin; Mohr, Kerstin; Haddad, Anneke; Elling, Roland; Lang, Peter; Rabsteyn, Armin; Jacobsen, Eva-Maria; Bode, Sebastian F. N.; et al. (Journal of medical virology, 2024)
The pivotal role of the cell entry receptor ACE2 for SARS-CoV-2 infection is well-established. When ACE2 is shed from cell surface into plasma as soluble ACE2 (sACE2), it can effectively neutralize SARS-CoV-2. This longitudinal prospective cohort study analyzed sACE2 activity in 1192 participants, aged 4 months to 81 years, 3 and 12 months after SARS-CoV-2 household exposure. Following SARS-CoV-2 exposure, participants exhibited significantly elevated sACE2 activity, irrespective of confirmed infection, with the highest levels observed in exposed children. Longitudinal analysis revealed a decline in sACE2 levels over time, reaching levels comparable to age- and sex-matched pre-pandemic controls. An increase in sACE2 activity was also confirmed in vitro in Calu-3 (human lung) cells within hours of SARS-CoV-2 exposure, providing a direct link between SARS-CoV-2 exposure and elevated sACE2. This study, therefore, challenges the dichotomy of categorizing SARS-CoV-2 exposed participants as infected or not infected solely on currently established diagnostic assays. It demonstrates lasting host responses independent of B- and T-cell memory and may help to keep SARS-CoV-2 infections in balance and contribute to successful virus clearance in children and adults lacking humoral and cellular immune responses following SARS-CoV-2 exposure. Trial Registration: German Registry for Clinical Studies; Identifier: D 00021521.
Online verfügbar: 03. Dezember 2024
Gesehen am 18.07.2025